Agenda 21 local e sustentabilidade socioambiental urbana de Limeira/SP - Capparol, Daniela Cristina Aparecida [UNESP] (2015)
This research has the hipothesis established the claim that the social and environmental problems verified (ineficiente public transport, large numbers of vehicles, congestion on main roads, disrespect for pedestrian, cyclists and motorcyclists, areas subjects to floods, failure to disclosure on the selective waste collection service, reparion deforestation in urban water bodies, inefficiency in the health services of the municipality, insecurity and urban among others) in the city of Limeira/SP, are due to failures in the development/implementation of programs/projects developed by local authorities, and therefore is a need to think of new prignosals in a large structure, that is, belonging to the Local Agenda 21. Considering this threshold, did where appropriate, through a questionaire prepared for this purpose a survey of programs/projects developed by the municipality of Limeira/SP in 2011 and 2012, being the last years of an administration of eight years and, mainly, because in 2013 other administration began and so, was limited to the development of new projects. Armed with this first survey, made it important to analyse the results (positive or not) of these actions from the point of the view of the urban population. To this, other questionaire was elaborated (with open, closed and dependente issues) and applied together with the inhabitants of this town (Association and Neighborhood Committees, schools with Youth and Adult Education and neighborhoods of greater acessibility to the research). The main notes made by the population were problems in traffic and transportation, small share of the population in cultural events and courses, selective collection service unheralded waste, little knowledge of the population about the Project Recycling Point and it's benefits, pollution and deforestation of urban water bodies, urban insecurity, deficiency in public health services of the population in sports municipal order and few...